Investigation of the Efficiency of Shielding Gamma and Electron Radiation Using Glasses Based on TeO2-WO3-Bi2O3-MoO3-SiO to Protect Electronic Circuits from the Negative Effects of Ionizing Radiation - Kozlovskiy, Artem; Shlimas, Dmitriy I.; Zdorovets, Maxim V.; Popova, Elena; Elsts, Edgars; Popov, Anatoli I. (MDPI, 2022)
This article considers the effect of MoO3 and SiO additives in telluride glasses on the shielding characteristics and protection of electronic microcircuits operating under conditions of increased radiation background or cosmic radiation. MoO3 and SiO dopants were chosen because their properties, including their insulating characteristics, make it possible to avoid breakdown processes caused by radiation damage. The relevance of the study consists in the proposed method of using protective glasses to protect the most important components of electronic circuits from the negative effects of ionizing radiation, which can cause failures or lead to destabilization of the electronics. Evaluation of the shielding efficiency of gamma and electron radiation was carried out using a standard method for determining the change in the threshold voltage (∆U) value of microcircuits placed behind the shield and subjected to irradiation with various doses. It was established that an increase in the content of MoO3 and SiO in the glass structure led to an increase of up to 90% in the gamma radiation shielding efficiency, while maintaining the stability of microcircuit performance under prolonged exposure to ionizing radiation. The results obtained allow us to conclude that the use of protective glasses based on TeO2–WO3–Bi2O3–MoO3–SiO is highly promising for creating local protection for the main components of microcircuits and semiconductor devices operating under conditions of increased background radiation or cosmic radiation. © 2022 by the authors.--//-- This is an open access article Kozlovskiy A., Shlimas D.I., Zdorovets M.V., Popova E., Elsts E., Popov "Investigation of the Efficiency of Shielding Gamma and Electron Radiati licence.on Using Glasses Based on TeO2-WO3-Bi2O3-MoO3-SiO to Protect Electronic Circuits from the Negative Effects of Ionizing Radiation", Materials (2022), 15 (17), art. no. 6071, DOI: 10.3390/ma15176071 under the CC BY 4.0
This research was funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (No. AP09058081). EP, EE, and AIP thank the Institute of Solid State Physics, University for their support. ISSP UL as the Center of Excellence is supported through the Framework Program for European universities Union Horizon 2020, H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; gamma radiation; microelectronics; protective materials; shielding; telluride glasses